Determination of 47 Pesticide Residues in Tea by QuEChERS Method Combined with Ultra Performance Liquid Chromatography-Tandem Mass Spectrometry - Huawen LIU; Meiqing DENG; Beiyan CHEN (Shipin gongye ke-ji, 2024)
An analysis method for simultaneous determination of 47 kinds of pesticide residues in tea was established by QuEChERS method combined with ultra performance liquid chromatography-tandem mass spectrometry. The samples were extracted by acetonitrile containing 1% acetic acid, and purified by QuEChERS method. The 47 pesticides were determined by ultra performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) with an electrospray ion source (ESI±) in positive and negative ion switching multiple reaction monitoring (MRM), and quantified by matrix-matched external standard method. Method validation revealed satisfactory linearities with correlation coefficients (r) between 0.9971 and 0.9996, and limits of detection were 0.001~0.006 mg/kg while the limits of quantitation were 0.002~0.020 mg/kg, the average recoveries at three spiked levels were in the range of 73.4%~114.3%, with relative standard deviations (n=6) of 0.3%~19.9%. The method is sensitive, accurate, stable, and can meet the requirements for determination of 47 pesticide residues in tea.